SiC substrate and SiC composite substrate
Patent Information
- Application Number
- CN202280095382.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
SiC substrates are prone to cracking and cracking during processing, resulting in a decrease in yield, and the prior art is difficult to effectively solve this problem.
A SiC substrate with a biaxially oriented SiC layer is used. In X-ray morphology measurement or optical microscopy observation, the ratio of the number of BPDs with an absolute value of 15° or less to the total number of BPDs with an absolute value of 15° or less in the acute angle side of the angle formed by the [11-20] direction is controlled.
By controlling the progress direction and density of base surface dislocations, the cracks and cracks of SiC substrates during processing are significantly reduced and the yield rate is improved.
Smart Images

Figure CN119654452A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a SiC substrate and a SiC composite substrate. Background Art
[0002] SiC (silicon carbide) has attracted much attention as a wide bandgap material that can control high voltage and high power with low loss. In particular, in recent years, power semiconductor devices using SiC materials (SiC power devices) have been superior in miniaturization, low power consumption, and high efficiency compared to power devices using Si semiconductors, and are therefore expected to be used in a variety of applications. For example, by using SiC power devices, converters, inverters, on-board chargers, etc. used in electric vehicles (EVs) and plug-in hybrid electric vehicles (PHEVs) can be miniaturized to improve efficiency. Therefore, the development of SiC chips that constitute the main body of SiC power devices has attracted much attention.
[0003] In order to make SiC power devices, it is necessary to make SiC single crystal epitaxially grow on SiC single crystal substrate. There are a large number of dislocations in the obtained SiC single crystal substrate, which are roughly divided into three types: through screw dislocations, through edge dislocations and basal plane dislocations (BPD). Among these dislocations, basal plane dislocations will be transferred to the epitaxial growth film. If they exist in the driving area of the device, the basal plane dislocations will expand into stacking defects due to power-on, which will have an adverse effect on the reliability of the SiC device. Patent document 1 (Japanese Patent Publication No. 2014-162649) discloses a SiC substrate, which is a SiC substrate having a main surface inclined at an off-angle from a plane perpendicular to the c-axis. For more than 80% of the basal plane dislocations on the surface of the main surface, the angle between the dislocation line direction and the deviation direction of the off-angle is greater than 45° and less than 90°. It is recorded that: if epitaxial growth is performed on the main surface of the SiC substrate, the basal plane dislocation on the main surface of the SiC substrate is not transferred to the epitaxial layer, and therefore, the basal plane dislocation of the epitaxial layer is suppressed. In addition, it is known that: cracking or cracking occurs when processing a SiC single crystal substrate. Non-patent document 1 (Y.Qiusheng, C.Senkai and P.Jisheng, "Surface and subsurface cracks characteristics of single crystal SiC wafer insurface machining," AIP Conference Proceedings 1653, 020091 (2015)) records: various processing is performed on single crystal SiC wafers, and the crack characteristics generated on the wafer surface are analyzed.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2014-162649
[0007] Non-patent literature
[0008] Non-patent document 1: Y.Qiusheng, C.Senkai and P.Jisheng, "Surface and subsurfacecracks characteristics of single crystal SiC wafer in surface machining," AIPConference Proceedings 1653,020091(2015) Summary of the invention
[0009] According to the disclosure of non-patent document 1, SiC is extremely hard and difficult to process, and the cracks and fissures that occur during grinding, polishing, and cutting of wafers have caused a reduction in yield. The direct cause is still unclear, but it may be related to deformation within the crystal, such as plastic deformation caused by dislocations. That is, it is not sufficient to simply reduce the basal plane dislocations (BPD) in the substrate, and it is expected to reduce the cracks and fissures during substrate processing such as grinding, polishing, and cutting.
[0010] The inventors of the present invention have recently obtained the following insight: by providing a SiC substrate with the following biaxially oriented SiC layer, cracking and fissures during substrate processing such as grinding, polishing and cutting can be reduced, and with respect to the biaxially oriented SiC layer, when performing X-ray morphology (XRT) measurement or optical microscope observation, the ratio of the number of BPDs whose absolute value of the acute angle side of the angle formed by the propagation direction of the BPD and the [11-20] direction is less than 15° to the total number of BPDs is controlled.
[0011] Therefore, an object of the present invention is to provide a SiC substrate capable of reducing cracks and fissures during substrate processing.
[0012] According to the present invention, the following solutions are provided.
[0013] [Solution 1]
[0014] A SiC substrate comprising a biaxially oriented SiC layer,
[0015] The SiC substrate is characterized in that
[0016] The SiC substrate and the biaxially oriented SiC layer have an off-angle,
[0017] In an XRT image obtained by X-ray topography (XRT) measurement of a certain 4 mm square area in the biaxially oriented SiC layer, the number of basal plane dislocations (BPDs) having an absolute value of 15° or less on the acute side of the angle formed between the direction of propagation of the BPDs and the [11-20] direction relative to the total number of the BPDs is 60% or more,
[0018] The direction of the BPD progression is defined as the direction of a line segment connecting an end point of the BPD observed as a line in the XRT image and a point 150 μm away from the end point along the linear BPD.
[0019] [Solution 2]
[0020] A SiC substrate comprising a biaxially oriented SiC layer,
[0021] The SiC substrate is characterized in that
[0022] The SiC substrate and the biaxially oriented SiC layer have an off-angle,
[0023] In an optical microscope image obtained by observing a plane inclined at the off-angle from the (0001) plane after KOH etching in a certain 4 mm square region of the biaxially oriented SiC layer, the number of basal plane dislocations (BPDs) having an absolute value of 15° or less on the acute angle side of the angle formed between the direction of propagation of the BPDs and the [11-20] direction relative to the total number of the BPDs is 70% or more,
[0024] The progression direction of the BPD is defined as the direction of the major axis of the elliptical pit determined in the optical microscope image.
[0025] [Solution 3]
[0026] The SiC substrate according to claim 1 or 2, characterized in that
[0027] The rare earth element concentration of the biaxially oriented SiC layer is 1.0×10 14 ~5.0×10 15 atoms / cm 3 .
[0028] [Solution 4]
[0029] The SiC substrate according to any one of items 1 to 3, characterized in that
[0030] The N concentration of the biaxially oriented SiC layer is 1.0×10 18 ~5.0×10 19 atoms / cm 3 .
[0031] [Solution 5]
[0032] The SiC substrate according to any one of claims 1 to 4, characterized in that
[0033] The B concentration of the biaxially oriented SiC layer is 1.0×10 15 ~1.0×10 18 atoms / cm 3 .
[0034] [Solution 6]
[0035] The SiC substrate according to any one of claims 1 to 5, characterized in that
[0036] In the optical microscope image obtained by observing the surface tilted at the off-angle from the (0001) surface after KOH etching of the biaxially oriented SiC layer, the density of oval etch pits including BPD was 50 / cm 2 The following 5mm square area.
[0037] [Solution 7]
[0038] A SiC composite substrate, characterized by comprising:
[0039] SiC single crystal substrate; and
[0040] The SiC substrate according to any one of claims 1 to 6 on the SiC single crystal substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a longitudinal cross-sectional view of the SiC composite substrate 10 .
[0042] Figure 2 It is a manufacturing process diagram of the SiC composite substrate 10 .
[0043] Figure 3 1 is a conceptual diagram showing the configuration of an aerosol deposition (AD) device 50 .
[0044] Figure 4 is an X-ray topography (XRT) image of the biaxially oriented SiC layer in Example 1.
[0045] Figure 5 This is an optical microscope image obtained by observing the plane of the biaxially oriented SiC layer in Example 1 which is tilted at an off angle from the (0001) plane. DETAILED DESCRIPTION
[0046] SiC substrate
[0047] The SiC substrate of the present invention comprises a biaxially oriented SiC layer, and the SiC substrate and the biaxially oriented SiC layer have an off-angle. With respect to the biaxially oriented SiC layer, in an XRT image obtained by performing X-ray topography (XRT) measurement on a certain 4 mm square area in the biaxially oriented SiC layer, the ratio P of the number of BPDs whose absolute value of the acute angle side of the angle formed by the propagation direction of the basal plane dislocation (BPD) and the [11-20] direction is 15° or less to the total number of BPDs is BPD,XRT (%) is 60% or more. Here, the direction of BPD progression is defined as the direction of a line segment obtained by connecting the end point of the BPD observed as a line and a point 150 μm away from the end point along the linear BPD in the XRT image. Alternatively, with respect to a biaxially oriented SiC layer, in an optical microscope image obtained by observing a surface inclined at an off-angle from the (0001) plane after KOH etching in a certain 4 mm square area of the biaxially oriented SiC layer, the number of BPDs whose absolute value of the acute angle side of the angle formed by the progression direction of the basal plane dislocation (BPD) and the [11-20] direction is 15° or less relative to the total number of BPDs is the ratio P BPD,KOH (%) is 70% or more. Here, the direction of BPD progression is defined as the direction of the long axis of the elliptical pit determined in the optical microscope image. It should be noted that the 4 mm square area mentioned above refers to the area in the direction of the plate surface of the biaxially oriented SiC layer. BPD,XRT or P BPD,KOH The area with the above ratio is defined as a "4 mm square area". However, in the present application specification, the area P in the "4 mm square area" is defined as BPD,XRT or P BPD,KOH When the ratio is as above, it can be considered that: in the entire area of the biaxially oriented SiC layer, P BPD,XRT or P BPD,KOH By providing the SiC substrate with a biaxially oriented SiC layer as follows, cracking and fissures during substrate processing such as grinding, polishing, and cutting can be reduced, and the ratio of the number of BPDs whose absolute value of the acute angle side of the angle between the BPD's propagation direction and the [11-20] direction is 15° or less relative to the total number of BPDs is controlled when performing X-ray morphology (XRT) measurement or optical microscope observation.
[0048] As described above, SiC is extremely hard and difficult to process, and the reduction in yield caused by cracks and fissures generated during grinding, polishing, and cutting of wafers has become a problem. That is, it is not sufficient to simply reduce the basal plane dislocations (BPD) in the substrate, and it is desirable to reduce cracks and fissures during substrate processing such as grinding, polishing, and cutting. In this regard, according to the present invention, this problem can be well eliminated.
[0049] Regarding the biaxially oriented SiC layer included in the SiC substrate of the present invention, in an XRT image obtained by performing XRT measurement on a certain 4 mm square area in the biaxially oriented SiC layer, P BPD,XRT is more than 60%. BPD,XRT It may be 70% or more, 80% or more, or 90% or more. BPD,XRT The upper limit of is not particularly limited, and is typically 100%. Alternatively, in the optical microscope image of the biaxially oriented SiC layer, after KOH etching of a 4 mm square region in the biaxially oriented SiC layer, the P BPD,KOH is more than 70%. BPD,KOH It may be 80% or more, or 90% or more. BPD,KOH The upper limit of is not particularly limited, but is typically 100%. BPD,XRT or P BPD,KOH , which can more effectively reduce cracking and cracking during substrate processing.
[0050] In the optical microscope image of the biaxially oriented SiC layer of the SiC substrate of the present invention obtained by observing the surface inclined at an off-angle from the (0001) surface after KOH etching of the biaxially oriented SiC layer, it is preferred that the density of oval etch pits as BPD is 50 / cm 2 The density of the BPD can be 1 to 40 / cm 2 , can also be 1 to 10 / cm 2 . It should be noted that the above-mentioned 5 mm square area refers to: the area in the plate surface direction of the biaxially oriented SiC layer. In addition, although the area where the BPD density is the above-mentioned density is set as the "5 mm square area", in the present application specification, when the BPD density in the "5 mm square area" is the above-mentioned density, it can be regarded as: in the entire area of the biaxially oriented SiC layer, the BPD density is the above-mentioned density. In this way, the SiC substrate of the present invention can reduce the BPD in the biaxially oriented SiC layer, and reduce the cracking and cracking during the substrate processing such as grinding, polishing, and cutting. In addition, with respect to the SiC substrate (specifically the biaxially oriented SiC layer) with the above-mentioned BPD density, it can be said that there are fewer BPDs in the substrate, and the absolute value of the acute angle side of the angle between the direction of progression of most BPDs and the [11-20] direction is less than 15°, so it is considered that the deformation in the crystal is reduced. As a result, not only can the cracking and cracking during substrate processing be reduced, but also the yield rate during substrate manufacturing can be improved.
[0051] When the SiC substrate or the biaxially oriented SiC layer has an off angle, the off angle is preferably 0.1 to 12°, more preferably 1 to 5°, with respect to the
[0001] axis of the SiC substrate or the biaxially oriented SiC layer.
[0052] Examples of rare earth elements contained in the biaxially oriented SiC layer include Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sc, and combinations thereof. The rare earth element is preferably Y or Ce, and more preferably Y, from the viewpoint of reducing cracks and fissures.
[0053] The rare earth element concentration of the biaxially oriented SiC layer is preferably 1.0×10 14 ~5.0×10 15 atoms / cm 3 , more preferably 5.0×10 14 ~5.0×10 15 atoms / cm 3 , more preferably: when Y is included, 5.0×10 14 ~1.4×10 15 atoms / cm 3 , when Ce is included, it is 5.0×10 14 ~4.0×10 15 atoms / cm 3 The N concentration of the biaxially oriented SiC layer is preferably 1.0×10 18 ~5.0×10 19 atoms / cm 3 , more preferably 1.0×10 18 ~2.0×10 19 atoms / cm 3 , and more preferably 1.0×10 18 ~1.0×10 19 atoms / cm 3 The B concentration of the biaxially oriented SiC layer is preferably 1.0×10 15 ~1.0×10 18 atoms / cm 3 , more preferably 2.0×10 15 ~1.0×10 17 atoms / cm 3 By setting the concentration of the rare earth element, N or B to be within the above range, the direction and density of BPD can be effectively controlled.
[0054] The biaxially oriented SiC layer is preferably oriented along the c-axis direction and the a-axis direction. In addition, the SiC substrate is preferably composed of a biaxially oriented SiC layer. The biaxially oriented SiC layer can be oriented along the biaxial directions of the c-axis and the a-axis, and can be a SiC single crystal, a SiC polycrystal, or a mosaic crystal. Mosaic crystal refers to a collection of crystals that have no obvious grain boundaries, but the orientation of the crystal is slightly different in one or both of the c-axis and the a-axis. The evaluation method of the orientation is not particularly limited, for example, known analysis methods such as the EBSD (Electron Back Scatter Diffraction Patterns) method and the X-ray pole diagram can be used. For example, when the EBSD method is used, the inverse pole figure mapping of the surface (plate surface) of the biaxially oriented SiC layer or the cross section orthogonal to the plate surface is measured. In the obtained inverse pole figure mapping, when the following four conditions (A) to (D) are met, it can be defined as biaxial orientation along the approximate normal direction and the approximate plate surface direction, (A) oriented in a specific direction (first axis) along the approximate normal direction of the plate surface, (B) oriented in a specific direction (second axis) in the approximate plate surface direction orthogonal to the first axis, (C) the tilt angle relative to the first axis is distributed within ±10°, (D) the tilt angle relative to the second axis is distributed within ±10°. In other words, when the above four conditions are met, it is judged to be biaxially oriented along the c-axis and the a-axis. For example, when the approximate normal direction of the plate surface is oriented along the c-axis, the approximate plate surface direction can be oriented along a specific direction (such as the a-axis) orthogonal to the c-axis. The biaxially oriented SiC layer can be biaxially oriented along the approximate normal direction and the approximate plate surface direction, but it is preferred that the approximate normal direction is oriented along the c-axis. When the tilt angle distribution in the approximate normal direction and / or the approximate in-plane direction is small, the mosaic property of the biaxially oriented SiC layer becomes smaller, and the closer it is to zero, the closer it is to a single crystal. Therefore, from the perspective of the crystallinity of the biaxially oriented SiC layer, the tilt angle distribution is preferably smaller in both the approximate normal direction and the approximate in-plane direction, for example, more preferably less than ±5°, and further preferably less than ±3°.
[0055] SiC composite substrate
[0056] The SiC substrate of the present invention is preferably in the form of a SiC composite substrate. That is, according to a preferred embodiment of the present invention, a SiC composite substrate comprising a SiC single crystal substrate and the above-mentioned SiC substrate on the SiC single crystal substrate is provided. In this way, by having the SiC composite substrate comprising the following SiC substrate, cracking and cracking during substrate processing can be reduced, wherein the SiC substrate comprises a biaxially oriented SiC layer, and with respect to the biaxially oriented SiC layer, when performing X-ray morphology (XRT) measurement or optical microscope observation, the ratio of the number of BPDs whose absolute value of the acute angle side of the angle formed by the direction of BPD progression and the [11-20] direction is less than 15° relative to the total number of BPDs is controlled.
[0057] Typically, the SiC single crystal substrate is a layer composed of SiC single crystals and has a crystal growth surface. The SiC single crystal substrate preferably has an off-angle. The polytype, off-angle and polarity of the SiC single crystal are not particularly limited, and the polytype is preferably 4H or 6H, the off-angle is preferably 0.1 to 12° relative to the
[0001] axis of the single crystal SiC, and the polarity is preferably the Si plane. More preferably, the polytype is 4H, the off-angle is 1 to 5° relative to the
[0001] axis of the single crystal SiC, and the polarity is the Si plane.
[0058] The SiC substrate of the present invention can be in the form of a self-supporting substrate with only a biaxially oriented SiC layer, or in the form of a SiC composite substrate accompanied by a SiC single crystal substrate. Therefore, as needed, the biaxially oriented SiC layer can be finally separated from the SiC single crystal substrate. The separation of the SiC single crystal substrate can be carried out by a known method, and is not particularly limited. For example, there can be cited: a method of separating a biaxially oriented SiC layer using a wire saw, a method of separating a biaxially oriented SiC layer using discharge machining, a method of separating a biaxially oriented SiC layer using a laser, etc. In addition, in the case of epitaxially growing a biaxially oriented SiC layer on a SiC single crystal substrate, the SiC single crystal substrate can be separated and then the biaxially oriented SiC layer can be set on another supporting substrate. The material of the other supporting substrate is not particularly limited, and from the perspective of material properties, an ideal material can be selected. For example, from the perspective of thermal conductivity, there can be cited: metal substrates such as Cu, ceramic substrates such as SiC, and AlN, etc.
[0059] Method for manufacturing SiC composite substrate
[0060] The SiC composite substrate with a SiC substrate of the present invention can be well manufactured as follows: (a) forming a predetermined oriented precursor layer on a SiC single crystal substrate; (b) heat-treating the oriented precursor layer on the SiC single crystal substrate to convert at least a portion of the oriented precursor layer near the SiC single crystal substrate into a SiC substrate (a biaxially oriented SiC layer); and (c) performing grinding, polishing, or other processing as desired to expose the surface of the biaxially oriented SiC layer. However, the manufacturing method of the SiC composite substrate is not limited, and the P BPD,XRT or P BPD,KOH A SiC substrate controlled to a specific ratio can be used. For example, it can be a gas phase method such as CVD or sublimation, or a liquid phase method such as a solution method. Rare earth elements, B and / or N can be added by the method described later. According to such a manufacturing method, a P BPD,XRT or P BPD,KOH A SiC substrate having a biaxially oriented SiC layer controlled to a specific ratio can effectively reduce cracking and fissures during processing of the SiC substrate or a SiC composite substrate using the SiC substrate.
[0061] Hereinafter, a preferred method for producing a SiC composite substrate will be described. Figure 1 is a longitudinal cross-sectional view of the SiC composite substrate 10 (a cross-sectional view when the SiC composite substrate 10 is longitudinally cut along a plane including the central axis of the SiC composite substrate 10 ), Figure 2 It is a manufacturing process diagram of the SiC composite substrate 10 .
[0062] like Figure 1 As shown, the SiC composite substrate 10 of the present embodiment includes a SiC single crystal substrate 20 and a SiC substrate 30 (corresponding to the SiC substrate of the present invention) on the SiC single crystal substrate.
[0063] (a) Formation step of alignment precursor layer
[0064] like Figure 2 As shown in (a) of FIG. 1 , the orientation precursor layer 40 becomes the SiC substrate (biaxially oriented SiC layer) 30 by a heat treatment described later. In the step of forming the orientation precursor layer 40 , the orientation precursor layer 40 is formed on the crystal growth surface of the SiC single crystal substrate 20 .
[0065] The method for forming the oriented precursor layer 40 can adopt a known method. Regarding the method for forming the oriented precursor layer 40, for example, there can be cited: solid phase film forming methods such as AD (aerosol deposition) method, HPPD (supersonic plasma particle deposition method), sputtering method, evaporation method, sublimation method, various CVD (chemical vapor growth) methods and other gas phase film forming methods, solution growth method and other liquid phase film forming methods, and a method of directly forming the oriented precursor layer 40 on the SiC single crystal substrate 20 can be used. As a CVD method, for example, a thermal CVD method, a plasma CVD method, a spray CVD method, an MO (organic metal) CVD method, etc. can be used. In addition, as the oriented precursor layer 40, a polycrystalline body pre-made by a sublimation method, various CVD methods, sintering, etc. can be used, and a method of placing it on the SiC single crystal substrate 20 can also be used. Alternatively, it can be a method of pre-making a molded body of the oriented precursor layer 40 and placing the molded body on the SiC single crystal substrate 20. Such an oriented precursor layer 40 may be a cast body produced by tape casting, or may be a green compact produced by pressure molding such as uniaxial pressing.
[0066] When forming the above-mentioned oriented precursor layer 40, it is preferred that the raw material of the oriented precursor layer 40 contains a rare earth compound. Accordingly, the concentration of the rare earth compound in the biaxially oriented SiC layer can be controlled. As the rare earth compound, there is no particular limitation, and oxides, nitrides, carbides and fluorides of at least one of the above-mentioned 17 rare earth elements can be cited. As the rare earth compound, it is preferably an oxide of a rare earth element, and more preferably an oxide of Y (yttrium oxide) and an oxide of Ce (cerium oxide). In addition, the concentration of B in the biaxially oriented SiC layer can be controlled as follows: adjusting the amount of boron or a boron compound (such as boron carbide) added to the raw material, pre-sintering the raw material, and evaporating metallic boron toward the SiC single crystal. In addition, depending on the type of carrier gas used when forming the oriented precursor layer 40 (such as He or N 2 ), which can effectively control the angle between the progression direction of BPD and the [11-20] direction.
[0067] It should be noted that in the method of directly forming the oriented precursor layer 40 on the SiC single crystal substrate 20, when various CVD methods, sublimation methods, solution growth methods, etc. are used, epitaxial growth sometimes occurs on the SiC single crystal substrate 20 without undergoing the heat treatment process described later, and the SiC substrate 30 is formed in a film shape. However, the oriented precursor layer 40 is in an unoriented state when it is formed, that is, it is amorphous or non-oriented polycrystalline, and it is preferably oriented with SiC single crystal as a seed in the subsequent heat treatment process. In this way, the crystal defects reaching the surface of the SiC substrate 30 can be effectively reduced. The reason is not clear, but it is believed that the rearrangement of the crystal structure produced by the oriented precursor layer of the solid phase of the temporary film formation with SiC single crystal as a seed is effective in eliminating crystal defects. Therefore, when using various CVD methods, sublimation methods, solution growth methods, etc., it is preferred to select conditions under which epitaxial growth does not occur in the formation process of the oriented precursor layer 40.
[0068] However, it is preferred to use an AD method or various CVD methods to directly form an oriented precursor layer 40 on a SiC single crystal substrate 20, or to place a polycrystal separately made by a sublimation method, various CVD methods, sintering, etc. on a SiC single crystal substrate 20. By using these methods, an oriented precursor layer 40 can be formed in a relatively short time. The AD method does not require a high vacuum process, and the film forming speed is relatively fast, so it is particularly preferred. In the method of using a pre-made polycrystal as an oriented precursor layer 40, in order to improve the adhesion between the polycrystal and the SiC single crystal substrate 20, it is necessary to smooth the surface of the polycrystal in advance. Therefore, from the perspective of cost, a method of directly forming an oriented precursor layer 40 is preferred. In addition, a method of placing a pre-made molded body on a SiC single crystal substrate 20 is also preferred as a simple method, but since the oriented precursor layer 40 is composed of powder, a process for sintering it in the heat treatment step described later is required. Any method can use known conditions, but the following describes a method of directly forming the orientation precursor layer 40 on the SiC single crystal substrate 20 by AD or thermal CVD and a method of placing a prefabricated molded body on the SiC single crystal substrate 20.
[0069] The AD method is a technique for forming a film by mixing particles or a particle raw material with a gas to form an aerosol and then spraying the aerosol from a nozzle at high speed to hit a substrate. The film can be formed at room temperature. An example of a film forming device (AD device) used in such an AD method is shown in FIG. Figure 3 . Figure 3The AD device 50 shown is configured as a device used in an AD method of spraying raw material powder onto a substrate in an atmosphere of a gas pressure lower than the atmospheric pressure. The AD device 50 includes: an aerosol generating unit 52 that generates an aerosol of raw material powder containing a raw material component; and a film forming unit 60 that sprays the raw material powder onto the SiC single crystal substrate 20 to form a film containing the raw material component. The aerosol generating unit 52 includes: an aerosol generating chamber 53 that stores the raw material powder and receives a carrier gas supplied from a gas cylinder not shown to generate an aerosol; a raw material supply pipe 54 that supplies the generated aerosol to the film forming unit 60; and a vibration exciter 55 that applies vibration to the aerosol generating chamber 53 and the aerosol therein at a vibration frequency of 10 to 100 Hz. The film forming unit 60 includes: a film forming chamber 62 in which aerosol is sprayed toward the SiC single crystal substrate 20; a substrate holder 64 disposed inside the film forming chamber 62 and fixing the SiC single crystal substrate 20; and an X-Y stage 63 that moves the substrate holder 64 in the X-axis-Y-axis direction. In addition, the film forming unit 60 includes: an injection nozzle 66 having a slit 67 formed at the front end thereof and spraying the aerosol toward the SiC single crystal substrate 20; and a vacuum pump 68 that decompresses the film forming chamber 62. The injection nozzle 66 is attached to the front end of the raw material supply pipe 54.
[0070] Regarding the AD method, it is known that pores are generated in the film depending on the film forming conditions, or the film becomes a powder compact. For example, it is easily affected by the impact speed of the raw material powder toward the substrate, the particle size of the raw material powder, the aggregation state of the raw material powder in the aerosol, the injection amount per unit time, etc. The impact speed of the raw material powder toward the substrate is affected by the differential pressure in the film forming chamber 62 and the injection nozzle 66, the opening area of the injection nozzle, etc. Therefore, in order to obtain a dense oriented precursor layer, it is necessary to appropriately control these factors.
[0071] In the thermal CVD method, a known film forming apparatus such as a commercially available film forming apparatus can be used as the film forming apparatus. The raw material gas is not particularly limited, and silicon tetrachloride (SiCl 4 ) gas, silane (SiH 4 ) gas, methane (CH 4 ) Gas, propane (C 3 H 8 ) gas, etc. The film forming temperature is preferably 1000 to 2200°C, more preferably 1100 to 2000°C, and further preferably 1200 to 1900°C.
[0072] It is known that when a film is formed on a SiC single crystal substrate 20 using a thermal CVD method, epitaxial growth sometimes occurs on the SiC single crystal substrate 20 to form a SiC substrate 30. However, the oriented precursor layer 40 is in an unoriented state when it is made, that is, it is amorphous or non-oriented polycrystalline, and it is preferably allowed to rearrange its crystals using a SiC single crystal as a seed during the heat treatment process. It is known that the formation of an amorphous or polycrystalline layer on a SiC single crystal using a thermal CVD method is affected by the film formation temperature, the gas flow rate of the Si source and the C source and their ratio, the film formation pressure, etc. The film formation temperature has a greater influence. From the perspective of forming an amorphous or polycrystalline layer, the film formation temperature is preferably lower, preferably less than 1700°C, more preferably below 1500°C, and further preferably below 1400°C. However, if the film formation temperature is too low, the film formation rate itself is also reduced. Therefore, from the perspective of the film formation rate, the film formation temperature is preferably higher.
[0073] When a prefabricated molded body is used as the orientation precursor layer 40, the orientation precursor raw material powder can be molded to produce it. For example, when press molding is used, the orientation precursor layer 40 is a press molded body. The press molded body can be produced by press molding the raw material powder of the orientation precursor based on a known method, for example, by placing the raw material powder in a mold at a pressure of preferably 100 to 400 kgf / cm 2 , more preferably 150 to 300 kgf / cm 2 It can be made by pressing with a pressure of. In addition, the molding method is not particularly limited. In addition to compression molding, tape casting, extrusion molding, casting molding, scraper method and any combination thereof can be used. For example, when tape casting is used, it is preferred to appropriately add additives such as binders, plasticizers, dispersants, dispersion media to the raw material powder to make it slurry, and pass the slurry through a slit-shaped finer nozzle, thereby ejecting and forming it into a sheet. The thickness of the molded body formed into a sheet is not limited, and from the perspective of operability, it is preferably 5 to 500 μm. In addition, when a thicker oriented precursor layer is required, multiple pieces of the sheet-like molded bodies can be stacked and used with the desired thickness. Regarding these molded bodies, the part near the SiC single crystal substrate 20 is converted into a SiC substrate 30 by subsequent heat treatment on the SiC single crystal substrate 20. In this method, it is necessary to sinter the molded body in the heat treatment step described later. It is preferred to form the SiC substrate 30 after the molded body is sintered and the process of becoming a polycrystalline body and the SiC single crystal substrate 20 is integrated. In a state where the molded body has not been sintered, epitaxial growth using the SiC single crystal as a seed may not occur sufficiently. Therefore, the molded body may contain additives such as a sintering aid in addition to the SiC raw material.
[0074] (b) Heat treatment process
[0075] like Figure 2 As shown in (b), in the heat treatment process, the stacked body stacked or loaded with the oriented precursor layer 40 on the SiC single crystal substrate 20 is heat treated, thereby generating a SiC substrate 30. As for the heat treatment method, there is no particular limitation as long as epitaxial growth with the SiC single crystal substrate 20 as the seed occurs, and it can be implemented in a known heat treatment furnace such as a tubular furnace and a hot plate. In addition, not only these heat treatments under normal pressure (no pressing) can be used, but also pressurized heat treatments such as hot pressing and HIP, and a combination of normal pressure heat treatment and pressurized heat treatment can be used. The atmosphere for the heat treatment can be selected from vacuum, nitrogen, inert gas and their combination atmospheres. At this time, the concentration of N in the biaxially oriented SiC layer can be controlled by adjusting the amount of nitrogen in the atmosphere during the heat treatment. The heat treatment temperature is preferably 1700 to 2700°C. By increasing the temperature, the oriented precursor layer 40 is easily grown along the c-axis and a-axis orientation edges with the SiC single crystal substrate 20 as the seed edge. Therefore, the heat treatment temperature is preferably above 1700°C, more preferably above 1800°C, further preferably above 1900°C, and particularly preferably above 2200°C. On the other hand, if the temperature is too high, it is possible that part of the SiC disappears due to sublimation, or SiC undergoes plastic deformation and produces undesirable conditions such as warping. Therefore, the heat treatment temperature is preferably below 2700°C, more preferably below 2500°C. However, the heat treatment conditions affect the concentrations of rare earth elements, N and B in the biaxially oriented SiC layer, so it is preferred to appropriately control the conditions (e.g., heat treatment temperature, holding time). From this point of view, the heat treatment temperature is preferably 1900-2700°C, more preferably 2200-2600°C, and further preferably 2400-2500°C. In addition, the holding time is preferably 2-30 hours, more preferably 4-20 hours. In addition, the heat treatment can be carried out in multiple stages. For example, it can be implemented under conditions such as heat treatment at 1950°C for 3 hours in a nitrogen atmosphere and then heat treatment at 2400°C for 3 hours in an argon atmosphere. Even in such a case, the heat treatment temperature and the total holding time are preferably within the above range. In addition, the heat treatment temperature and holding time are also related to the thickness of the SiC substrate 30 generated during epitaxial growth and can be appropriately adjusted.
[0076] However, when a prefabricated molded body is used as the orientation precursor layer 40, it needs to be sintered by heat treatment, preferably by normal pressure sintering, hot pressing, HIP or a combination thereof at a high temperature. For example, when hot pressing is used, the surface pressure is preferably 50 kgf / cm 2 More preferably, 100 kgf / cm 2 More preferably, 200 kgf / cm 2Above, there is no particular upper limit. In addition, regarding the firing temperature, similarly, there is no particular limitation as long as sintering and epitaxial growth occur. However, the firing conditions affect the concentrations of rare earth elements, N and B in the biaxially oriented SiC layer, so it is preferred to appropriately control the conditions (such as firing temperature, holding time). From this point of view, the firing temperature is preferably 1700-2700°C. In addition, the holding time is preferably 2-18 hours. The atmosphere during firing can be selected from vacuum, nitrogen, an inert gas atmosphere, or a mixed gas of nitrogen and an inert gas. In addition, as described above, firing can be carried out in multiple stages, and the firing temperature and the total holding time are preferably within the above range. The SiC powder constituting the raw material can be composed of at least one of α-SiC and β-SiC, preferably β-SiC. The SiC powder is preferably composed of SiC particles having an average particle size of 0.01-100 μm. The average particle size refers to an average value of the maximum oriented diameters of 100 primary particles measured by observing the powder with a scanning electron microscope.
[0077] During the heat treatment process, the crystals in the oriented precursor layer 40 grow along the c-axis and a-axis orientations from the crystal growth surface of the SiC single crystal substrate 20, so that the oriented precursor layer 40 gradually changes from the crystal growth surface to the SiC substrate 30. The SiC composite substrate having the generated SiC substrate 30 becomes a substrate with reduced cracking and fissures during substrate processing.
[0078] (c) Grinding and / or lapping processes
[0079] like Figure 2 As shown in (c) in FIG. 1 , in the grinding step, the oriented precursor layer 40 remaining on the SiC substrate 30 after the heat treatment step is ground away to expose the surface of the SiC substrate 30 , and the exposed surface is ground and / or polished. Thus, the SiC composite substrate 10 is obtained.
[0080] It should be noted that the present invention is not limited to the above-mentioned embodiments, and of course, it can be implemented in various schemes as long as it belongs to the technical scope of the present invention. For example, in the above-mentioned embodiment, only one layer of SiC substrate 30 is provided on the SiC single crystal substrate 20, but two or more layers may be provided. Specifically, the oriented precursor layer 40 is stacked on the SiC substrate 30 of the SiC composite substrate 10, and after heat treatment, grinding and / or polishing are performed in sequence, thereby a second layer of SiC substrate 30 can be provided on the SiC substrate 30.
[0081] Example
[0082] The present invention will be further specifically described by the following examples.
[0083] Example 1
[0084] (1) Preparation of oriented precursor layer
[0085] Prepare a raw material powder containing 90.8 wt% of commercially available fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 8.1 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm), and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm). Use SiC balls to mix these raw material powders in ethanol in a ball mill for 24 hours and dry them to obtain a mixed powder. As a SiC single crystal layer, prepare a commercially available SiC single crystal substrate (n-type 4H-SiC, diameter of about 100 mm (4 inches), Si plane, (0001) plane, off-angle 4°, thickness 0.35 mm, no orientation flat (Orientation Flat)), and Figure 3 In the AD device 50 shown, a mixed powder is sprayed onto a SiC single crystal substrate to form an AD film (oriented precursor layer).
[0086] The AD film forming conditions are as follows. First, the carrier gas is set to He, and a ceramic nozzle with a slit of 5 mm long side × 0.4 mm short side is used for film forming. Regarding the scanning conditions of the nozzle, the scanning speed of 0.5 mm / s is repeated to move 105 mm in the direction perpendicular to and forward of the long side of the slit, 5 mm in the direction of the long side of the slit, 105 mm in the direction perpendicular to and returning to the long side of the slit, and 5 mm in the direction of the long side of the slit and in the opposite direction to the initial position. At the moment of moving 105 mm from the initial position along the long side of the slit, scan in the opposite direction to the previous direction and return to the initial position. Such a cycle is set as 1 cycle, and it is repeated 4000 cycles. The thickness of the AD film formed in this way is about 400 μm.
[0087] (2) Heat treatment of the orientation precursor layer
[0088] The SiC single crystal substrate on which the AD film as the orientation precursor layer was formed was taken out from the AD device and annealed at 2400° C. for 10 hours in an argon atmosphere. That is, the orientation precursor layer was heat-treated to obtain a heat-treated layer.
[0089] (3) Grinding
[0090] (3a) Surface grinding
[0091] The (0001) surface of the SiC single crystal substrate having the heat-treated layer formed thereon was surface-ground to a predetermined thickness using a grinding device (diamond wheel with a grit number of 1000 to 6000) to achieve the target thickness and surface condition.
[0092] (3b) Back grinding
[0093] The (000-1) surface of the SiC single crystal substrate on which the heat-treated layer was formed was surface-ground to a predetermined thickness using a grinding device (diamond wheel with a grit number of 1000 to 6000) to obtain a SiC substrate.
[0094] (4) Cracking and cracking ratio after processing
[0095] An industrial microscope (ECLIPSE LV150N manufactured by Nikon) was used, and the magnification of the eyepiece was set to 10 times, and the magnification of the objective lens was set to 5 times. The entire surface of the SiC substrate obtained in the above (3) was observed in polarization mode and differential interference mode. When cracks or cracks were confirmed, the substrate was deemed to have cracks or cracks. At this time, only the cases where the length of cracks and cracks was 100 μm or more were counted as cracks and cracks. The number of SiC substrates with cracks and cracks with a length of 100 μm or more in 100 SiC substrates manufactured under the same conditions as the SiC substrate manufactured as described above was calculated, and the incidence rate P of cracks and cracks was calculated. C (%). By finding the P C The yield rate of the substrate was evaluated. The results are shown in Table 1.
[0096] (5) Cutting of SiC substrate
[0097] After the evaluation of (4) above, the SiC substrate without cracks or fissures was cut with a diamond saw and processed into a chip shape of about 5 mm×5 mm.
[0098] (6) Grinding
[0099] (6a) Surface grinding
[0100] The (0001) surface of the chip-shaped SiC substrate obtained in the above (5) is polished with diamond abrasive grains and then finished by chemical mechanical polishing (CMP) to achieve the target thickness and surface condition.
[0101] (6b) Back grinding
[0102] The (000-1) surface of the chip-shaped SiC substrate obtained in the above (5) was polished with diamond abrasive grains to achieve the target thickness and surface condition.
[0103] (7) Evaluation of Biaxial Orientation of Heat-treated Layer
[0104] Using the EBSD (Electron Back Scatter Diffraction Patterns) method, the inverse pole figure mapping of the surface (plate surface) and the cross-section perpendicular to the plate surface of the heat-treated layer obtained in the above (3) was measured using the conditions shown below. As a result, the tilt angle distribution in the approximate normal direction and the approximate plate surface direction was less than 0.01°. Therefore, it was judged that the heat-treated layer was a biaxially oriented SiC layer oriented along the c-axis and the a-axis, and had the same off-angle as the SiC single crystal substrate.
[0105] <EBSD measurement conditions>
[0106] · Measurement device: SEM (SU-5000 manufactured by Hitachi High-Technologies Corporation) equipped with an electron backscatter diffraction device (EBSD) (Nordlys Nano manufactured by Oxford Instruments)
[0107] Accelerating voltage: 15kV
[0108] Light spot intensity: 70
[0109] Working distance: 22.5mm
[0110] · Step size: 0.5μm
[0111] · Sample tilt angle: 70°
[0112] ·Measurement program: Aztec (version 3.3)
[0113] (8) X-ray morphology (XRT) measurement of heat-treated layer
[0114] Chips (about 5 mm×5 mm) of the heat-treated layers (biaxially oriented SiC layers) prepared by the above (1) to (6) were used as evaluation samples, and XRT images of the evaluation samples were obtained under the conditions shown below.
[0115] <XRT measurement conditions>
[0116] ·Measurement device: X-ray topography imaging system (XRTmicron manufactured by Rigaku Corporation)
[0117] ·Measurement area: 4mm square area
[0118] Observation mode: 3D-XRT
[0119] Diffraction surface: (22-40) surface
[0120] X-ray source: Cu, Kα
[0121] Tube voltage / tube current: 40kV / 30mA
[0122] Detector: CCD camera
[0123] By superimposing 3D-XRT data, Figure 4 Among the linear contrasts observed in the XRT image, the linear contrasts with XRT intensities above the top 5% ( Figure 4 The arrows a and b) in the figure are regarded as BPDs, and the total number of BPDs is counted. Thus, the density C of BPDs in the 4 mm square area is calculated. BPD,XRT ( / cm 2 ). Then, the BPD ( Figure 4 The ratio of the number of arrows in a) to the total number of BPDs BPD,XRT (%). It should be noted that Figure 4 The arrow b in the figure indicates a BPD whose absolute value of the acute angle side of the above angle exceeds 15°. Here, the direction of the BPD progression is defined as the direction of the line segment obtained by connecting the end point of the BPD observed as a line in the XRT image and the point 150 μm away from the end point along the linear BPD. The results are shown in Table 1.
[0124] (9) Optical microscope observation of heat-treated layer
[0125] A chip (about 5 mm × 5 mm) of the heat-treated layer (biaxially oriented SiC layer) produced using the above (1) to (6) was used as an evaluation sample. The evaluation sample was placed in a nickel crucible together with the KOH crystal and etched in an electric furnace at 500°C for 10 minutes. The evaluation sample after etching was cleaned and an optical microscope was used to observe the surface inclined at an angle from the (0001) plane in a 4 mm square area of the heat-treated layer (biaxially oriented SiC layer) in the evaluation sample at a magnification of 50 times. In the optical microscope image, the total number of BPDs identified as elliptical etch pits was counted, and the density C of the BPDs in the 4 mm square area was calculated. BPD,KOH ( / cm 2 ). Then, the ratio P of the number of BPDs whose absolute value of the acute angle between the BPD's direction of advancement and the [11-20] direction is less than 15° to the total number of BPDs is calculated. BPD,KOH (%). The results are shown in Table 1. It should be noted that the direction of BPD progression is defined as the direction of the major axis of the elliptical pit determined in the optical microscope image. Here, an example of the observed BPD is shown in Figure 5 . Figure 5 Arrow a in the figure indicates a BPD whose absolute value of the acute angle between the BPD's direction of advancement and the [11-20] direction is less than 15°. Figure 5 The arrow b in FIG. 1 indicates a BPD in which the absolute value of the acute angle side of the above angle exceeds 15°.
[0126] (10) Concentrations of B, N, Y, and Ce in the Heat-treated Layer (Biaxially Oriented SiC Layer)
[0127] The chip (about 5 mm × 5 mm) of the heat-treated layer (biaxially oriented SiC layer) produced by the above (1) to (6) was used as the evaluation sample. Dynamic secondary ion mass spectrometry (D-SIMS) was performed on the (0001) surface of the polished surface of the evaluation sample. The analysis device for rare earth elements (in this case, Y and Ce) and B was IMS-7f manufactured by CAMECA, with primary ion seed O 2 + The measurement was carried out at an accelerating voltage of 11.0 kV. The N analysis apparatus used was IMS-7f manufactured by CAMECA, Inc., with the primary ion species Cs + The Y concentration C was measured at an acceleration voltage of 15.0 kV. Y (atoms / cm 3 ), Ce concentration C Ce (atoms / cm 3 ), the concentration of B C B (atoms / cm 3 ) and the concentration of N C N (atoms / cm 3 ). The results are shown in Table 1.
[0128] Example 2
[0129] In the above (1), a raw material powder containing 82.7 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 16.2 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0130] Example 3 (Compare)
[0131] In the above (1), a raw material powder containing 74.9 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 24.0 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0132] Example 4
[0133] In the above (1), a raw material powder containing 94.9 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 4.0 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0134] Example 5 (Compare)
[0135] In the above (1), a raw material powder containing 97.9 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 1.0 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0136] Example 6
[0137] In the above (1), a raw material powder containing 90.8 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 8.1 wt% of cerium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0138] Example 7
[0139] In the above (1), a raw material powder containing 82.7 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 16.2 wt% of cerium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0140] Example 8 (Compare)
[0141] In the above (1), a raw material powder containing 74.9 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 24.0 wt% of cerium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0142] Example 9
[0143] In the above (1), a raw material powder containing 94.9 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 4.0 wt% of cerium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0144] Example 10 (Compare)
[0145] In the above (1), a raw material powder containing 97.9 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 1.0 wt% of cerium oxide powder (volume-based D50 particle size: 0.1 μm) and 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0146] Example 11
[0147] In the above (1), a raw material powder containing 88.8 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 8.1 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm), 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) and 2.0 wt% of boron carbide powder (volume-based D50 particle size: 0.5 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0148] Example 12
[0149] In the above (1), a raw material powder containing 86.8 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 8.1 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm), 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) and 4.0 wt% of boron carbide powder (volume-based D50 particle size: 0.5 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0150] Example 13
[0151] In the above (1), a raw material powder containing 82.8 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 8.1 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm), 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) and 8.0 wt% of boron carbide powder (volume-based D50 particle size: 0.5 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0152] Example 14
[0153] In the above (1), a raw material powder containing 74.8 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 8.1 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm), 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) and 16.0 wt% of boron carbide powder (volume-based D50 particle size: 0.5 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0154] Example 15(Compare)
[0155] In the above (1), a raw material powder containing 58.8 wt% of fine β-SiC powder (volume-based D50 particle size: 0.7 μm), 8.1 wt% of yttrium oxide powder (volume-based D50 particle size: 0.1 μm), 1.1 wt% of silicon dioxide powder (volume-based D50 particle size: 0.7 μm) and 32 wt% of boron carbide powder (volume-based D50 particle size: 0.5 μm) was used, and the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0156] Example 16
[0157] In the above (2), a SiC substrate was prepared and evaluated in the same manner as in Example 1 except that the heat treatment atmosphere was 99.95% argon and 0.05% nitrogen. The obtained heat-treated layer was confirmed to be a biaxially oriented SiC layer. The results are shown in Table 1.
[0158] Example 17
[0159] In the above (2), a SiC substrate was prepared and evaluated in the same manner as in Example 1 except that the heat treatment atmosphere was 99.9% argon and 0.1% nitrogen. The obtained heat-treated layer was confirmed to be a biaxially oriented SiC layer. The results are shown in Table 1.
[0160] Example 18
[0161] In the above (2), a SiC substrate was prepared and evaluated in the same manner as in Example 1 except that the heat treatment atmosphere was 99.5% argon and 0.5% nitrogen. The obtained heat-treated layer was confirmed to be a biaxially oriented SiC layer. The results are shown in Table 1.
[0162] Example 19
[0163] In the above (2), except that the heat treatment atmosphere was 99.0% argon and 1.0% nitrogen, the SiC substrate was prepared and evaluated in the same manner as in Example 1. The obtained heat-treated layer was confirmed to be a biaxially oriented SiC layer. The results are shown in Table 1.
[0164] Example 20 (Compare)
[0165] In the above (2), except that the heat treatment atmosphere was 70.0% argon and 30.0% nitrogen, the SiC substrate was prepared and evaluated in the same manner as in Example 1. It was confirmed that the obtained heat-treated layer was a biaxially oriented SiC layer. The results are shown in Table 1.
[0166] [Table 1]
[0167]
[0168] Although the reason is still uncertain, it is known that the direction and density of BPD can be controlled by the carrier gas and the Y, Ce, N and B concentrations in the biaxially oriented SiC layer. In addition, it is known that the ratio of the number of BPDs whose absolute value of the acute angle formed by the direction of BPD and the [11-20] direction is less than 15° can control the ratio of cracks and cracks during processing. In particular, it is known that when the rare earth element concentration is 5.0×10 14 ~5.0×10 15 atoms / cm 3 , N concentration is 1.0×10 18 ~2.0×10 19 atoms / cm 3 and B concentration is 2.0×10 15 ~1.0×10 17 atoms / cm 3 In this case, cracking or fissures during processing can be reduced more effectively.
Claims
1. A SiC substrate comprising a biaxially oriented SiC layer, The SiC substrate is characterized in that The SiC substrate and the biaxially oriented SiC layer have an off-angle, In an XRT image obtained by performing X-ray topography (XRT) measurement on a certain 4 mm square area in the biaxially oriented SiC layer, the number of BPDs having an absolute value of 15° or less on the acute angle side of the angle formed between the direction of propagation of basal plane dislocations (BPDs) and the [11-20] direction relative to the total number of BPDs is 60% or more, The direction of the BPD progression is defined as the direction of a line segment connecting an end point of the BPD observed as a line in the XRT image and a point 150 μm away from the end point along the linear BPD.
2. A SiC substrate comprising a biaxially oriented SiC layer, The SiC substrate is characterized in that The SiC substrate and the biaxially oriented SiC layer have an off-angle, In an optical microscope image obtained by observing a plane tilted at the off-angle from the (0001) plane after KOH etching in a certain 4 mm square area of the biaxially oriented SiC layer, the number of BPDs having an absolute value of 15° or less on the acute angle side of the angle formed by the direction of propagation of basal plane dislocations (BPDs) and the [11-20] direction relative to the total number of BPDs is 70% or more, The progression direction of the BPD is defined as the direction of the major axis of the elliptical pit determined in the optical microscope image.
3. The SiC substrate according to claim 1 or 2, characterized in that: The rare earth element concentration of the biaxially oriented SiC layer is 1.0×10 14 ~5.0×10 15 atoms / cm 3 .
4. The SiC substrate according to claim 1 or 2, characterized in that: The N concentration of the biaxially oriented SiC layer is 1.0×10 18 ~5.0×10 19 atoms / cm 3 .
5. The SiC substrate according to claim 1 or 2, characterized in that: The B concentration of the biaxially oriented SiC layer is 1.0×10 15 ~1.0×10 18 atoms / cm 3 .
6. The SiC substrate according to claim 1 or 2, characterized in that: In the optical microscope image obtained by observing the surface tilted at the off-angle from the (0001) surface after KOH etching of the biaxially oriented SiC layer, the density of oval etch pits including BPD was 50 / cm 2 The following 5mm square area.
7. A SiC composite substrate, characterized in that: have: SiC single crystal substrate; and The SiC substrate according to claim 1 or 2 on the SiC single crystal substrate.
Citation Information
Patent Citations
SiC SUBSTRATE, PRODUCTION METHOD OF SiC SUBSTRATE, AND SiC EPITAXIAL SUBSTRATE
JP2014162649A